2016
DOI: 10.1038/srep31951
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing autocrine and paracrine signals in hematopoietic stem cell culture using a biofunctional microcavity platform

Abstract: Homeostasis of hematopoietic stem cells (HSC) in the mammalian bone marrow stem cell niche is regulated by signals of the local microenvironment. Besides juxtacrine, endocrine and metabolic cues, paracrine and autocrine signals are involved in controlling quiescence, proliferation and differentiation of HSC with strong implications on expansion and differentiation ex vivo as well as in vivo transplantation. Towards this aim, a cell culture analysis on a polymer microcavity carrier platform was combined with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 72 publications
(99 reference statements)
2
25
0
Order By: Relevance
“…Interestingly, characteristic t D of order 3000s (1 mg/mL hydrogel) did not show the same effect for HSC only cultures, while t D of order of 540s in the presence of Lin + niche cells was sufficient to promote paracrine signal mediated hematopoietic differentiation. These findings are conceptually consistent with those recently reported by Müller et al for culture of HSPCs in media filled microcavities; autocrine feedback promoted HSC quiescence but could also be abrogated by expanding the size of the microcavity to dilute the effect [26]. In our work, increasing the characteristic t D of fully three-dimensional hydrogels was able to promote autocrine-mediated HSC expansion, suggesting selective engineering of characteristic diffusion times provides an important avenue for hematopoietic stem cell niche engineering in fully three-dimensional biomaterial environments.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Interestingly, characteristic t D of order 3000s (1 mg/mL hydrogel) did not show the same effect for HSC only cultures, while t D of order of 540s in the presence of Lin + niche cells was sufficient to promote paracrine signal mediated hematopoietic differentiation. These findings are conceptually consistent with those recently reported by Müller et al for culture of HSPCs in media filled microcavities; autocrine feedback promoted HSC quiescence but could also be abrogated by expanding the size of the microcavity to dilute the effect [26]. In our work, increasing the characteristic t D of fully three-dimensional hydrogels was able to promote autocrine-mediated HSC expansion, suggesting selective engineering of characteristic diffusion times provides an important avenue for hematopoietic stem cell niche engineering in fully three-dimensional biomaterial environments.…”
Section: Discussionsupporting
confidence: 92%
“…From an engineering context, Zandstra et al demonstrated selective inhibition of paracrine and autocrine feedback signal transduction pathways in liquid culture to alter HSC fate [21,23,25]. Recently, Müller et al described the use of arrays of microcavities to culture single or small groups of hematopoietic stem and progenitor cells (HSPCs), and reported that while autocrine feedback within the microcavity culture may play a role in HSC quiescence, paracrine signaling provided both stimulatory and inhibitory effects [26]. While these studies highlight the importance of autocrine and paracrine signaling mechanisms for HSC biomanufacturing, significant opportunity exists to develop a framework to examine the balance of these signals within a fully-3D biomaterial platform where matrix diffusive transport plays a critical role.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic [89]. However, it is also important to consider the influence of heterotypic cell-cell interactions within more complex niche mimics.…”
Section: Discussionmentioning
confidence: 99%
“…http://dx.doi.org/10.1101/289553 doi: bioRxiv preprint first posted online Mar. 27, 2018; paracrine signaling from proximal MSCs mediate HSC activation and quiescence through production of factors such as CXCL12 [32], IL-6 [33,34], and TPO [35] that regulate HSC activity via diffusive signaling and direct cell-cell contact [6,28,31,[36][37][38][39]. While co-cultures of HSCs and MSCs within a hydrogel matrix offer the opportunity to identify heterotypic cultures that support HSC quiescence or self-renewal, such studies are significantly complicated by the dynamic reciprocity between inhabiting cells and the surrounding matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation